Accounting Information System (AIS) Adoption in Small and Medium-sized Enterprises in Northern Ghana - Fuseini Mahama; Halina Mohamed Dahlan (Contemporary Research in Business, Management and Economics Vol. 1, 2024)
Accounting Information Systems (AIS), a technology-based system, provide decision-makers with timely and reliable information. The study examines the factors influencing small and medium-sized enterprises (SMEs) AIS adoption in Northern Ghana, where little is known about it. Direct content analysis was used to collect data, and summative content analysis was used to generate research findings. A detailed literature review was conducted first, followed by a problem confirmation process involving academic researchers. The study concentrated on the factors that influence Small and Medium Scale Enterprises (SMEs) AIS adoption in Ghana. For the sake of credibility, data was collected from previous studies using prominent educational databases. Studies on AIS adoption in Ghana have revealed a lack of effectiveness. Rather of being integrated, adoption theories are either based on technology, organisations, and environment or based on humans, organisations, and technology; however, neither of these ideas integrates human, organisation, technology, and the environment. The study found a link between AIS adoption and SMEs’ performance as measured by IT officers’ innovativeness, competency knowledge, IT infrastructure, managerial structure, organizational readiness, and competitive pressure from human, organizational, technological, and environmental dimensions. This address SMEs adoption of AIS factors. The study contributes to SMEs AIS adoption which is relatively new in Ghana. It also contributes to the sparse literature on SMEs’ AIS adoption by employing four dimensions to widen knowledge. However, to make data more representative, future studies in this field should involve samples from other regions.